APPLICATION OF SELF-TALK TECHNIQUE TO OVERCOME INTERPERSONAL COMMUNICATION BARRIERS OF BLIND CLIENT H - Rahayu, Intan; Noviza, Neni; Marianti, Lena (LP2M IAI Al-Khairat Pamekasan, 2025)
This study aims to determine the application of self-talk techniques in overcoming barriers to interpersonal communication in client